Detecção e correção de situações de deadlock em workflow nets interorganizacionais - Silva, Luciane de Fátima (2014)
In this work, an approach based on Deadlock avoidance of Interorganizational Work-Flow nets is proposed to deal with these situations. Interorganizational business processes are modeled by Interorganizational WorkFlow nets. Deadlock situations in interorganizational business processes come generally related to losses during message exchanges between several business processes. Within the Petri net theory, a Deadlock situation is characterized by the presence of a siphon that can be empty. After detecting and controlling the Siphon structures that lead to Deadlock situations in Interorganizational WorkFlow nets, a method for the design of Interorganizational WorkFlow nets free of Deadlock is proposed. In particular, the basic principle is to dene new Work- Flow nets shared among the original work ow processes that allow one to remove the scenarios responsible for the Deadlocks.